Analisis Pendapatan Usahatani Ubi Kayu pada Lahan Sub Optimal di Kecamatan Binongko Kabupaten Wakatobi - Umliyah, Gamar; Bahari, Bahari; Limi, Muhammad Aswar (Jurnal Ilmiah Membangun Desa dan Pertanian, 2019)
The income from cassava farming in Sub Optimal in the District of Binongko, Wakatobi Regency. The research was conducted in Rukuwa Village, Wali Village, Wakarumende Village, Lagongga Village, and Jaya Makmur Village Binongko Subdistrict, Wakatobi Regency. The Cassava Agriculture in Binongko Subdistrict, which is identified as many as 120 heads of cassava is based on observational data from researchers at the research site. The samples were carried out by purposive sampling or intentional samples. . from 5 villages by taking 25% of the total population of 30 chiefs of cassava farmers in 5 villages in Binongko District. This is done by researchers, it is homogeneous (similar) or has the same character. The variables are related to the economic aspects, the costs incurred from the beginning of the land processing to harvest, the receipt of cassava farming and cassava farming income and analyzed using income analysis. Based on the results of the study, the average income from farmers can be seen from the production of cassava produced is valued at Rp.860,116.68 / planting season.